TiO2:(Fe, S) Thin Films Prepared from Complex Precursors by CVD, Physical Chemical Properties, and Photocatalysis - V. G. Bessergenev; M. C. Mateus; D. A. Vasconcelos; J. F. M. L. Mariano; A. M. Botelho do Rego; R. Lange; E. Burkel (International Journal of Photoenergy)
The TiO2 thin films were prepared using Ti(dpm)2(OPri)2 and Ti(OPri)4 (dpm = 2,2,6,6-tetramethylheptane-3,5-dione, Pri = isopropyl) as the precursors. The volatile compounds Fe[(C2H5)2NCS2]3 and [(CH3)C]2S2 were used to prepare doped TiO2 films. The synthesis was done in vacuum or in the presence of Ar and O2. The pressure in the CVD chamber was varied between 1.2×10−4 mbar and 0.1 mbar, with the system working either in the molecular beam or gas flow regime. Physical, chemical, and photocatalytic properties of the (Fe, S)-doped TiO2 films were studied. Those TiO2:(Fe, S) films prepared from the Ti(OPri)4 precursor show increased photocatalytic activities, very close to those of Degussa P25 powder in UV region.